Manipulation through Legal and Judicial Translation Process - Bilero, Anila (Mediterranean Journal of Social Sciences, 2012)
In the context of the general translating as a process, that today in the consecutive epoch of globalizing processes who hadinvolved the modern society, the legal and justice translation has been done and he as well as an essential and common; however isclearly visible how little importance and attention, to say the least, is devoted from the criticism or contemporary literature. In translator’senvironments, often we listen the italian expression "tratuttore, traditore" that means "translator, traitor". Many translators have had theirexperiences, good or bad, encountered during the translation process. Legal texts and judicial, legally regarded as "original" and not astranslated; we really never used the term translation, otherwise it will be affected very important principle of authenticity, which wouldmean that each of the texts been translated depend on the interpretation of the courts. One of the more used practices of translations ofthe legal texts is the method of translation ëith the same vieë of language in ëhich is translated. Pierre Pescatore says that "The idealtranslation of the EU legislation is that can be read as it was originally drafted in this language." The requirements of translations in thecourtroom are legally and complex interpretations that aimed to achieved the inter-language and inter-cultural equivalence. As above,and not only, will be the subject of this paper!